Serological responses to vaccination in children exposed in utero to ustekinumab or vedolizumab: cross-sectional analysis of a prospective multicentre cohort - Mitrova, Katarina; Cerna, Karin; Zdychyncova, Kristyna; Pipek, Barbora; Svikova, Jana; Minarikova, Petra; Adamcova, Miroslava; David, Jan; Lukas, Milan; Duricova, Dana (European journal of pediatrics, 2024)
Evidence on serological responses to vaccination in children exposed to ustekinumab (UST) or vedolizumab (VDZ) in utero is lacking. This multicentre prospective study aimed to assess the impact of prenatal exposure to UST or VDZ due to maternal inflammatory bowel disease (IBD) on serological responses to vaccination and other immunological parameters in exposed children. Children aged ≥ 1 year who were exposed in utero to UST or VDZ and completed at least 1-year of mandatory vaccination were included. We assessed the serological response to vaccination (non-live: tetanus, diphtheria, and Haemophilus influenzae B; live: mumps, rubella, and measles), whole blood count, and immunoglobulin levels. The control group comprised unexposed children born to mothers without IBD. A total of 23 children (median age, 25 months) exposed to UST (n = 13) or VDZ (n = 10) and 10 controls (median age, 37 months) were included. The serological response to vaccination was comparable between the UST and VDZ groups and controls, with an adequate serological response rate of ≥ 80%. Only children exposed to UST showed a slightly reduced serological response to mumps (67% vs. 86% in controls), whereas all children exposed to VDZ showed an adequate response. The majority of the exposed children had normal levels of individual immunoglobulin classes, similar to the controls. No severe pathology was observed in any of the children.Conclusion: Despite the limited sample size, our findings suggest that in utero exposure to VDZ or UST does not significantly impair the vaccine response or broader immunological parameters in exposed children.
Keywords: dospělí; Female; Infant; předškolní dítě; Adult; mladý dospělý; ženské pohlaví; průřezové studie; Ustekinumab; vakcinace; Inflammatory Bowel Diseases; lidé; těhotenství; zpožděný efekt prenatální expozice; studie případů a kontrol; Prenatal exposure; Vaccination; gastrointestinální látky; prospektivní studie; Cross-Sectional Studies; Male; Case-Control Studies; kojenec; Prospective Studies; Child, Preschool; Young Adult; Prenatal Exposure Delayed Effects; Biologic treatment; idiopatické střevní záněty; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; mužské pohlaví; Gastrointestinal Agents; Pregnancy; Inflammatory bowel disease; ustekinumab; Humans